Translation Method in Song Lyric “Cintanya Aku” From Indonesian to English - Sihite, Rani Amelia; Marbun, Waldi; Hutabarat, Sabrina Wandani; Saragih, Frans Ananda (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
This study analyzes the translation methods in the lyrics of the song "Cintanya Aku" from Indonesian to English. In the process of translation analysis, the researcher uses the theory of translation methods based on Newmark's theory, namely word-for-word translation, literal translation, faithful translation, semantic translation, adaptation, free translation, idiomatic translation, and communicative translation. This research uses descriptive qualitative method in analyzing the data. The problems discussed in this study are: 1. What is the meaning of the lyrics of the song "Cintanya Aku" into English? 2. What translation method is used by the translator to translate the lyrics of the song "Cintanya Aku" into English? Finally, the researcher found that the most dominant method which is used by the translator is Free translation. This free translation prioritizes the overall meaning and impact of the source text over a direct word-for-word translation.